2022
DOI: 10.1002/ehf2.13918
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of pacing dependence and cardiac dysfunction in patients with permanent pacemaker implantation

Abstract: Aims Right ventricular pacing (RVP) dependence could impair left ventricular ejection fraction (LVEF). This study aimed to illuminate the relationship between RVP proportion and LVEF, as well as disclosing independent predictors of RVP dependence. Methods and resultsPatients indicated for permanent pacemaker implantation were included (2016-2020). The ventricular pacing lead was placed in right ventricular apex or septum. Pacing mode programming followed universal standard. Electrocardiographic, echocardiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Several previous investigators [ 1 14 ], including the authors’ previous report [ 2 ], found a significant association between pacemaker dependency in patients with CIED and second or third degree AV block at implant, age, male gender and heart failure severity as indexed by a higher NYHA functional class, reduced left ventricular ejection fraction and elevated brain natriuretic peptide. In addition, a twofold risk for pacemaker dependency in patients with CIED and chronic kidney disease compared to patients without chronic kidney disease was found [ 2 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several previous investigators [ 1 14 ], including the authors’ previous report [ 2 ], found a significant association between pacemaker dependency in patients with CIED and second or third degree AV block at implant, age, male gender and heart failure severity as indexed by a higher NYHA functional class, reduced left ventricular ejection fraction and elevated brain natriuretic peptide. In addition, a twofold risk for pacemaker dependency in patients with CIED and chronic kidney disease compared to patients without chronic kidney disease was found [ 2 ].…”
Section: Discussionmentioning
confidence: 97%
“…Although several previous [ 1 14 ] studies investigated the prevalence of pacing dependency following implantation of cardiovascular implantable electronic devices (CIEDs), only two previous studies [ 9 , 11 ] determined the prognostic significance of pacing dependency during follow-up. The results of these two previous studies [ 9 , 11 ], however, remained inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…To address these issues, pacing techniques involving the His bundle or the left bundle area have recently been introduced [ 4 , 5 ]. Many studies have compared the outcomes of these novel pacing techniques with those of conventional RVP [ 6 ] and investigated the factors contributing to the problems associated with RVP, with pacing rate and QRS duration reported as problematic factors [ 7 , 8 ]. However, to the best of our knowledge, studies of the relationship between RVP and mortality are limited.…”
Section: Introductionmentioning
confidence: 99%
“…To address these issues, pacing techniques involving the His bundle or left bundle area have been recently introduced [4,5]. Many studies have compared the outcomes of these novel pacing techniques with those of conventional RVP [6], and investigated the factors contributing to the problems associated with RVP, with pacing rate and QRS duration reported as problematic factors [7,8]. However, to the best of our knowledge, studies on the relationship between RVP and mortality are limited.…”
Section: Introductionmentioning
confidence: 99%